Electromagnetic wave propagation through an azimuthally perturbed helix - Basu B.N.; Jha R.K.; Sinha A.K.; Kishore L. (My University, 2025)
A field analysis is developed for the helical slow-wave structure of a traveling-wave tube in the anisotropic sheath helix model considering the effects of the azimuthal harmonics generated due to periodical positioning of the support bars around the helix. A practical relevance is added to the problem by way of considering the effect of an overall metal enclosure; the losses of the structure are, however, ignored. The analytical result justifies the usual heuristic approach of treating the support bars as a continuous dielectric of a suitably interpreted permittivity.